Analysis Government Regulation No. 24 Of 2016 On Changes Of Pp No. 37 Of 1998 On Regulation Of Title Deed Land Builders Officials (PPAT) Viewed From Public Service Perspective - Rahmi Rosyada Thoha; Amin Purnawan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
PPAT is a Public Officer who was given authority to make Authentic Acts concerning certain Legal Acts. The position setting originally stipulated in Government Regulation No. 37 of 1998 About the Position Rules PPAT. But the PP is then converted into PP No. 24 of 2016.Changes in the Articles of the regulation be deleted, changed, added and replaced to accommodate the social and technological development of society. Such changes of course have specific objectives and considerations. In one considering mentioned that the amendment is aimed at increasing the role of the PPAT as well as to improve services to the public relating to the Registration of Land.The purpose of this writing is to analyze Articles on Government Regulation No. 37 of 1998 which experienced Changes to Regulation No. 24, 2016. These changes are described and analyzed from the perspective of the Public Service.In essence there are two (2) Provisions that Changed Age Requirements to be PPAT the original 30 (thirty) years to 22 (twenty two) years and change the Working Area of Regency / City became the Province. Seen from the Perspective of Public Service, is aimed Positive Normative changes. Nevertheless Technical and Ethical Aspects always be a consideration in the implementation in the field.Keywords: PP No. 37 of 1998, PP No. 24 of 2016, Public Service, PPAT.